2023
DOI: 10.3390/ijerph20186785
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Behavior Practices and Compliance of Workers Exposed to Respirable Dust in a Zambian Copper Mine

Mwaba Sifanu,
Thomas K. Taylor,
Kennedy K. Kalebaila
et al.

Abstract: Work in the copper mining industry is often associated with exposure to respirable dust and respirable crystalline silica. This exposure has the potential to cause silicosis, an incurable occupational respiratory lung disease. This study aimed at establishing the relationship between knowledge, attitudes, work behavioral practices and compliance with safety standards and workers’ exposure to respirable dust. A cross-sectional descriptive survey was conducted on 528 mine workers. The Statistical Package for Soc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Dust exposure control is the only way to prevent workers from developing silica-related diseases; as highlighted above, dust control measures range in their effectiveness according to the hierarchy of controls. However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ].…”
Section: The Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Dust exposure control is the only way to prevent workers from developing silica-related diseases; as highlighted above, dust control measures range in their effectiveness according to the hierarchy of controls. However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ].…”
Section: The Hostmentioning
confidence: 99%
“…However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ]. Moreover, educating workers has a direct impact on their proper use of prevention practices such as the effective use of personal protective respiratory equipment, which may prevent worsening of pulmonary function due to reduced dust exposure [ 64 ].…”
Section: The Hostmentioning
confidence: 99%